PENGEMBANGAN BAHAN AJAR ELBOO AUVIS (ELEKTRONIK BOOK AUDIO VISUAL) PEMBELAJARAN PPKN KELAS X SMA - Meizura, Ella; Santoso, Minto; Baihaqi, M. Iqbal (LPPM Institut Pendidikan Nusantara Global, 2023)
Teaching materials are any form of tools used by teachers in the learning process that provide information to students in accordance with the applied curriculum reference. Based on interviews with teachers from three schools, including SMAN 1 Blitar, SMAN 3 Blitar, and SMAN 4 Blitar, a change from the 2013 Curriculum to the Merdeka Curriculum was found, especially in class (X), to enhance student learning after the Covid-19 pandemic. During the learning process, teachers faced challenges in the form of varying levels of student enthusiasm. The use of printed books such as school textbooks and Student Worksheets (LKS) resulted in students being less interested in reading thick books. Based on these issues, the researcher became interested in developing an instructional material product in the form of an e-book and evaluating the feasibility of the developed product. The research subjects were Civic Education teachers and students of Class X in senior high school. Data collection techniques included product validation sheets and usage response questionnaires. The results of this study showed the development of the ELBOO AUVIS (Electronic Book Audio Visual). The material expert validation percentage was 98.4%, categorized as highly valid; the media expert validation was 85.5%, also highly valid; and the language expert validation was 90%, again highly valid. In the teacher's usage response test, the average percentage obtained was 94.5%, categorized as a very good assessment, while the student's usage response obtained an average percentage of 90.2%, also categorized as very good.